Skeptisme Profesional Memoderasi Pengaruh Audit Training Pada Kemampuan Deteksi Kecurangan - Mirah Pradnya Ningrat Pemayun, Cok Istri; Dwirandra, A.A. Ngurah Bagus (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
The purpose of this study is to obtain empirical evidence of the positive influence of training audits on fraud detection capabilities, and professional skepticism to strengthen the positive influence of training audits on fraud detection capabilities. This research was conducted at the Bali Provincial Public Accountants Office registered with the Indonesian Institute of Certified Public Accountants. The population of this research is all auditors who work in KAP in Bali Province. The sample is determined using the purposive sampling method. The method of data collection is done using the questionnaire method and the data analysis techniques used are multiple linear analysis and moderated regression analysis. Based on the analysis it was found that audit training had a positive effect on lack of detection ability, and professional skepticism was able to strengthen the effect of audit training on fraud detection capabilities. Keywords: Fraud detection capabilities, audit training, and professional skepticism